Case series of type III hyperlipoproteinemia in children. (9th June 2011) - Fung, Michelle; Hill, John; Cook, Donald; Frohlich, Jiri
Abstract : Type III hyperlipoproteinemia (type III HLP) rarely manifests in childhood. Long-term follow-up (37 years) of the first patient revealed hypothyroidism at diagnosis requiring thyroxine replacement, palmar xanthomas requiring surgical removal, splenomegaly requiring splenectomy, 18 episodes of pancreatitis and premature coronary artery disease. Investigation revealed an apolipoprotein E phenotype of E2/E2 and partial lipoprotein lipase deficiency. Investigation of the second patient revealed a combination of apoE2/E2 phenotype and heterozygous familial hypercholesterolaemia. The third patient had a complete deficiency of lipoprotein lipase activity, an abnormal thyroid stimulating hormone on diagnosis (with subsequent normalisation without treatment), and apoE2/E2 phenotype. Type III HLP is a serious disorder with lifelong consequences of premature vascular disease and recurrent pancreatitis. Early presentation of disease in our patients was associated with additional precipitating factors. Drug treatment of paediatric type III HLP is indicated if dietary modifications alone are insufficient in managing the dyslipidaemia.